AloWeather - ICT tool for delivering agroadvisory service to farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Drawing on research from ACIS project and identifying opportunities, the first phase builds on existing partnerships with meteorological services and the DARD Extension Service; establishing new partnerships with Vietnamese IT-engineers who develop technical solutions. Second phase focuses on piloting the technology with adjustments and rolling out a full-scale service.